Metabolic syndrome and chronic kidney disease - Bhowmik, D. (Medknow Publications, 2008)
Obesity is fast becoming a bane for the present civilization, as a result of sedentary lifestyle, atherogenic diet, and a susceptible thrifty genotype. The concept of metabolic syndrome, which is a constellation of metabolic disturbances, has crystallized over the last 80 years with the aim of identifying those at greater risk of developing type 2 diabetes and cardiovascular disease. These patients have visceral obesity and insulin resistance characterized by hypertyriglyceridemia. Recently, it has been realized that they are also at an increased risk of chronic renal disease. Release of adipocytokines leads to endothelial dysfunction. There is also activation of systemic and local renin-angiotensin-aldosterone system, oxidative stress, and impaired fibrinolysis. This leads to glomerular hyperfiltration, proteinuria, focal segmental glomerulosclerosis (FSGS), and ultimately end-stage renal disease (ESRD). Treatment consists of lifestyle modifications along with optimal control of blood pressure, blood sugar and lipids. Metformin and thiazolidenidiones reduce insulin resistance; while angiotensin converting enzyme inhibitors and angiotensin receptor blockers reduce proteinuria and have a renoprotective effect. Exciting new medical therapies on the horizon include rimonabant a cannabinoid receptor type 1 antagonist, soy proteins, and peroxisome proliferator-activated receptor (PPAR) agonist. Bariatric surgery for morbid obesity has also been shown to be effective in treating metabolic syndrome.